Mental Health First Aid in Students with Psychosocial Problems Have Suicide’s Risk - Candra Aprilia Kartika; Ahmad Guntur Alfianto; Mizam Ari Kurniyanti (Jurnal Ilmu Keperawatan Jiwa, 2020)
Psychosocial problems (depression, anxiety and stress) in students causes to the risk of suicide. The effort can be done in school by providing first aid mental health First aid (MHFA) in students who have psychosocial problems with the risk of suicide. The purpose of this research is to analyze the influence of MHFA on psychosocial problems with the risk of suicide in one of the Malang High School. The research design uses an experimental-pretest-posttest with control group design with a sample totalling 30 students for the intervention group and 30 students for the control group. The sampling technique is used a purposive sampling . Instruments to assess psychosocial signs and symptoms in adolescents using the DASS 42 questionnaire. The Cronbach ’alpha value of the instrument is 0,942. The statistical tests used were Chi-square test, Wilcoxon test and Mann Whitney Test. The results is a decline in psychosocial problems (0.000) with the risk of suicide in one of the Malang High School. And there is a difference between the treatment group (MHFA) with the control group against the decline of psychosocial problems with suicide risk in one of the Malang High School.